2023
DOI: 10.1007/s10639-023-11778-6
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of university students to continue using e-Learning platforms after compelled adoption of technology: Test of an extended UTAUT model

Abstract: The COVID-19 pandemic has prompted the adoption of an e-Learning pedagogy. This forced teachers and students to shift to online learning and thus was compelled to adopt online educational technology. Educational institutes have been facing challenges like insufficient infrastructure and a shortage of quality teachers. Online learning can help to address these challenges as online classes can accommodate more students. However, before implementing e-Learning technology management of institutes wants to be sure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…First, we analyzed the outer loadings of indicators, composite reliability, and average variance extracted (AVE), which were analyzed for convergent validity. According to the research (Patil & Undale, 2023), optimal values for factor loadings, composite reliability, and AVE are above 0.7 and 0.5, respectively. The item loading weights are also recommended to be greater than or equal to 0.5 for the corresponding latent variables (Likhachev et al, 2020).…”
Section: Measurement Model Evaluationmentioning
confidence: 98%
See 1 more Smart Citation
“…First, we analyzed the outer loadings of indicators, composite reliability, and average variance extracted (AVE), which were analyzed for convergent validity. According to the research (Patil & Undale, 2023), optimal values for factor loadings, composite reliability, and AVE are above 0.7 and 0.5, respectively. The item loading weights are also recommended to be greater than or equal to 0.5 for the corresponding latent variables (Likhachev et al, 2020).…”
Section: Measurement Model Evaluationmentioning
confidence: 98%
“…The second sort of validity, known as discriminant validity (Patil & Undale, 2023), evaluates the degree to which one concept differs from all other constructs in the research model. The Fornell-Larcker criterion (i.e., the square root of AVE), cross-loadings, and the Heterotrait-Monotrait ratio of correlations (HTMT) are used to evaluate discriminant validity.…”
Section: Table 2 Convergent Validity and Composite Reliabilitymentioning
confidence: 99%
“…This framework used "performance expectancy, effort expectancy, social influence and facilitating conditions" to explore individuals' intentions regarding various technologies (Venkatesh et al, 2012). The researchers have adopted performance and effort expectancy as a construct based on prior literature recommendations (Patil and Undale, 2023). The rationale behind selecting performance expectancy is to examine the usefulness of ChatGPT for individuals.…”
Section: Diffusion Of Innovation and Unified Theory Of Acceptance And...mentioning
confidence: 99%
“…Besides, Strzelecki (2023) reported that EE significantly influences BI. However, several studies found that EE insignificantly impacts ATT (Chavez Herting et al, 2023) and BI (Patil and Undale, 2023). Hence, the authors proposed the following hypotheses:…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation